The advantages of computer-aided manufacturing integration in the production process of selected Philippine garment manufacturers - Dela Cruz, Jessica Lyn I.
Cutthroat competition in the global arena makes technology an integral part in a company's arsenal in its fight to gain competitive advantage. Thus, the introduction of advanced technology, specifically, Computer-Aided Manufacturing (CAM) Systems and Equipments offers a good armory to Philippine Garment Manufacturing Firms. CAM is a computer technology that enables manufacturers to significantly decrease production time by using computers to do formerly labor-intensive work (Calasibetta, 1998). The study was about the advantages of integrating Computer-Aided Manufacturing (CAM) in the production process of selected Philippine Garment Manufacturing Companies. It determined the characteristics of selected Philippines Garment Manufacturing Companies that utilize CAM, defined CAM and its uses in the production process of such companies, determined the advantages and disadvantages of using CAM and the extent of its application in these companies, and lastly, it evaluated the role of CAM in gaining competitive advantage. The study would be of help to garment manufacturing companies, people involved in the industry, and BS Clothing Technology Students towards gaining a better understanding of CAM and its influences on the production process. Also, the research activity contributed to the body of knowledge as a source of information. The research design used for the study was the multimethod design. Purposive sampling was used to determine the experts from six selected Philippine Garment Manufacturing Companies as respondents of the semistructured interview, which was facilitated with the use of an interview schedule/questionnaire. In addition, a marketing executive of CAM Systems and Equipments was interviewed. Findings showed that companies that utilize CAM equipments were mainly involved with high volume and value production and in the production of woven garments. CAM helped these companies by reducing costs, improving quality, and shortening lead time or turn-around of products. This way, CAM contributed to competitiveness. A cost benefit analysis illustrated CAM affecting competitiveness thru cost minimization. However, it was not for all companies to invest in. CAM has no market for the manufacture of knitted garments. Thus, CAM integration in the production process yielded positive results to companies that invest in it and although CAM equipments were costly, its benefits outweighed the large capital investment required.